Política industrial do Rio Grande do Sul (2012-2014): uma análise crítica - Vaz, Ibes Eron Alves (Universidade do Vale do Rio dos Sinos, 2014)
This research analyze critically the process of implementation and execution of the Rio Grande do Sul Industrial Policy (IP-RS), in the period 2012-2014. The work consist in an exploratory research, with documental and bibliographic survey. The Research Methodology was the Study of Single Case. The starting point was the literature review and the debate surrounding the concept of industrial policy, studying the conceptions of the schools of economic thought favorable and against the adoption of this kind of public policy. For the analyses of the Industry and the Nations Competitive Advantage, the referential is highly grounded in the thought of Michael Porter, who inspired the creation of the IP-RS. The main objectives of the work are: i) present the IP-RS and its main results in the studied period; ii) do the critic analyses of the Policy focusing the five axis that are part of the policy; and iii) suggest conceptual and practical elements that can contribute to the improvement and a bigger effectiveness of the IP-RS. The base for such an analyses is the field research made by the author, the data gathering of this research was made from semi-structured interviews with 51 relevant people, in the Rio Grande do Sul. The obtained results show many strengths and a general acceptance consistent with the Industrial Policy, as well as, a few divergent items, however, very pronounced, as for example, the focus of the IP-RS in relation to the selected sectors to receive the government support. The results can be used as a source of feedback for the public policies aimed to the economic development.
Keywords: Política industrial; Política industrial do Rio Grande do Sul; Desenvolvimento econômico; Políticas públicas; Industrial policy; Industrial policy of the Rio Grande do Sul; Economic development; Public policies; ACCNPQ::Engenharias::Engenharia de Produção